Lixo eletrônico nossa responsabilidade: uma oficina pedagógica para cursos técnicos em Informática da Educação Profissional e Tecnológica (EPT) - Oliveira, Fernanda Miranda de (Brasil, 2024)
There are several sources of electronic waste, including homes, companies and governments. This type of solid waste can contain precious metals such as gold, copper and nickel, as well as rare materials such as indium and palladium, and toxic substances such as heavy metals. Many of these materials can be recovered, recycled and reinserted into the production chain to manufacture new products. Inadequate disposal of electronic waste degrades the environment and harms the health of the population, due to the presence of heavy metals in the components of electronic boards, used in the manufacture of computers, cell phones, televisions, batteries, printers, among other electronic devices. . In Brazil, there are specific laws, decrees and resolutions for the management of this solid waste, aiming to mitigate environmental impacts and, consequently, risks to human health. In this context, the need to improve teaching on the topic of electronic waste in the technical computer course of Professional and Technological Education (EPT) becomes evident. The lack of teaching material that helps teachers to address the topic in the classroom, the theoretical and practical limitations of teaching strategies, the lack of knowledge among students and teachers regarding legislation, decrees, resolutions and standards that govern correct waste management electronic waste, as well as the chemical composition of this solid waste, are factors that reinforce this need. Understanding the potential environmental impacts of electronic waste and how to manage it effectively is essential for complete training. This pedagogical workshop aims to be a teaching resource to assist teachers in teaching the topic of electronic waste in EPT technical courses in the IT segment.